New method of trenchless cable replacement by the new HDD wash over technology - Hans-Joachim Bayer (Acta Montanistica Slovaca, 2007)
An enormous amount of underground electricity and telecommunication cables have become time-worn technical defects or need a capacity increase. Thus, new lines need to be installed. In urban areas, even in smaller communities and in nature reserves, open trenching is difficult and often not permitted.New patented methods of trenchless cable replacement by using the HDD equipment have been developed by the TT Group. The new technology is called “Wash-over-cable-replacement” and applies specially designed drill heads, reaming around the old cable string in various configurations (completely closed, U-shaped or sigmoidal embracing), depending on the coating structure of the old cable. The cable replacement drill heads separate the cable from adhesive or contacting soil or sand bedding, create a very small annular space around the cable which enables a pulling or dragging out of the old cable section between a start and an exit pit. After the old cable has been loosened from the surrounding soil by means of the wash over process and pulled out, the new cable is smoothly pulled into the void using the drill rods embedding the new cable into a rich bed of Bentonite.The replacement drill heads are slim and have inner and outer nozzles for Bentonite and bits in order to handle roots, pebbles, gravel and the like. These drill heads can very fast (up to 3 meters per minute) and effectively wash over existing cables without damaging the cable coating and prepare the ground for a fast new laying of a new cable in the existing line. Network owners also benefit from the fact that new geodetic or topographic surveys and documentations of the new cable are not necessary, only, the documents, remarks, technical codes and existing geodetic data need to be updated.The paper will outline the technological background and includes many practical job examples.